Gregory Peck : Universal Hollywood icons collection [videorecording (DVD)] - Peck, Gregory, 1916-2003; Loren, Sophia, 1934-; Badel, Alan; Moore, Kieron, 1924-2007; Matthau, Walter; Baker, Diane, 1938-; Curtis, Tony, 1925-2010; Dickinson, Angie; Albert, Eddie; Storch, Larry; Blyth, Ann, 1928-; Cotler, Gordon; et al. (Rovi Media Collection. Movies., 2016)
This collection of Gregory Peck films includes Arabesque, Mirage, Captain Newman, M.D., and The world in his arms.